Exploration of the utilization of fly ash in medicinal plant cultivation - Singh, Joginder; Raj, Seema; Kaur, Dilraj Preet (Frontiers in Sustainability, 2025)
Coal-fired thermal power plants remain the primary electricity source in much of the developing world, generating vast quantities of fly ash (FA) as a solid waste by-product. This ultrafine particulate contains heavy metals and, in some cases, radioactive elements, creating disposal challenges and raising concerns about environmental contamination, bioaccumulation, and human health risks. At the same time, fly ash is rich in plant-essential nutrients such as potassium, calcium, magnesium, and trace elements, and its application as a soil amendment can improve physical structure, nutrient availability, and biological activity. Research indicates that, when applied judiciously, fly ash can enhance plant growth, chlorophyll synthesis, phenolic compound content, and crop yield, including in medicinal species. However, the potential for toxic element transfer through the food chain necessitates rigorous risk assessment and management strategies. This study examines both the hazards and agronomic opportunities of FA, highlighting the importance of balancing environmental safety with the potential for sustainable agricultural use.